The Importance of Serum Procalcitonin in Diagnosis and Treatment of Serious Bacterial Infections and Sepsis - Mehanic, Snjezana (AVICENA, d.o.o., Sarajevo, 2013)
The clinical utility of serum procalcitonin (PCT) levels continues to evolve. PCT is regarded as a promising candidate marker for making a diagnosis and antibiotic stewardship in patients with systemic infections. The aim of this review is to summarize the current evidence for PCT in different infections and clinical settings, and to discuss the reliability of this marker when used with validated diagnostic algorithms.